Review of Bone, Bronze, and Bamboo: Unearthing Early China with Sarah Allan - Grebnyev, Georgiy (JAOS, 2025)
Bone, Bronze, and Bamboo: Unearthing Early China with Sarah Allan. Edited by Constance A. Cook, Christopher J . Foster, and Susan Blader. State University oF New York Press, 2024. Pp. xviii + 332. $198.